Genetics of inherited arrhythmias in pediatrics. Issue 6 (December 2015) - Campuzano, Oscar; Sarquella-Brugada, Georgia; Cesar, Sergi; Iglesias, Anna; Arbelo, Elena; Brugada, Josep; Brugada, Ramon
Abstract : Purpose of review: Recent international expert consensus statements have updated the clinical and genetic diagnoses of patients suffering from arrhythmogenic diseases. However, a lack of genotype–phenotype correlations has hampered the development of a risk stratification scale for sudden cardiac death. Recent findings: The improvement in the field of genetics has prompted the discovery of new genes associated with sudden cardiac death. Sudden cardiac death is a socially devastating event, especially when it occurs in the pediatric population. Physical activity can often trigger the arrhythmia and sudden death may be the first symptom. These inherited cardiac diseases may be difficult to diagnose, leaving family members also at risk. Thanks to the development of new high-throughput technologies, genetics may be used in the diagnosis of these diseases and even cases that remain unexplained after a comprehensive autopsy. Genetic testing cannot only identify the causative genetic variant in the index case, but it enables the detection of relatives at risk of sudden death, despite remaining clinically asymptomatic. Summary: We review the recent advances in the genetics of inherited arrhythmias associated with sudden cardiac death. We focus on the pediatric population, the main group of people suffering from lethal inherited arrhythmias.